Tempest in a K-Cup: Red flags on Green Mountain - Caplan, D.; Dutta, Saurav; Marcinko, D. (American Accounting Association, 2017)
© 2017, American Accounting Association. All rights reserved. “Tempest in a K-Cup” chronicles financial reporting challenges faced by Green Mountain Coffee Roasters, Inc. during a period of rapid growth following its acquisition of Keurig. The case focuses on events during 2011–2012, a period in which Green Mountain experienced significant stock price volatility, was challenged by the Securities and Exchange Commission (SEC) about its business relationships and financial disclosures, and was subject to highly publicized scrutiny by a well-known hedge-fund manager, David Einhorn, of Greenlight Capital. Students completing the case will apply accounting guidance and perform financial statement analysis to gain an appreciation for the scrutiny that companies receive from regulators, investors, and journalists. The case and its requirements are designed to be used in intermediate accounting, financial statement analysis, forensic accounting, and accounting capstone courses.